Generative AI-Driven Innovation in Digital Identity Verification: Leveraging Neural Networks for Next-Generation Financial Security - Murali Malempati (Utilitas Mathematica, 2024)
Generative AI is a potent force behind many exciting innovations in digital identity verification. Specifically, new kinds of neural networks apply to a range of issues around giving people secure access to valuable services. These innovations challenge the field of digital identity verification to embrace them and expand from merely preventing impersonation to also serving a range of other needs in new ways with a similarly broad range of technologies. Financial services offer a notable example of video-based identification that is being approached in innovative new ways. The coinciding range of methods exemplifies the diversity in methods of digital identity verification, from token-based technologies to knowledge-based technologies, something that offers an additional layer of privacy and security benefits when lending itself to a contextual approach, which AI-informed generative video methods are easily capable of producing reasonable results. Given past findings that half of institutions are likely to implement generative video ID methods next year, only 60% of representatives view existing methods as strong. The arrival of generative AI technologies brings with it an opportunity to innovate for digital identity. This opportunity is a strong strategic asset needed to meet the current pain points of customers being asked to submit sensitive data twice or expected to furnish state or national identity details, which, if tied up in a massive breach, has the potential to seriously exacerbate the financial world's exposure to crime while it provides a reproduction path for large-scale identity theft and perpetration of identity crimes. A highly correlated driver is the lack of secure password protection.